2016
DOI: 10.15171/jcs.2016.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Reactions among Patients with Chronic Hepatitis B: a Qualitative Study

Abstract: Introduction: Hepatitis B is the most prevalent type of viral hepatitis. Psychological reactions among patients with hepatitis B infection is considerably different and affects their decision about treating and following up the disease. The present study aims at explaining the psychological demonstrations experienced by these patients. Methods: In this qualitative study, a total of 18 patients with hepatitis B (8 women and 10 men) were selected by purposive sampling method. Data were collected by unstructured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 18 publications
8
41
0
Order By: Relevance
“…A similar lack of knowledge about hepatitis has been reported in many studies (Ng, Low, Wong, Sudin, & Mohamed, ; Wallace, Mcnally, Richmond, Hajarizadeh, & Pitts, ). The feeling of stigmatization revealed in the present study is compatible with the findings of previous qualitative studies showing stigma in patients of HBV infection in Iran (Hassanpourdehkordi et al., ; Valizadeh et al., ). Patients’ stigmatization‐related perceptions and responses vary across communities, diseases (Butt, ) and periods of time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A similar lack of knowledge about hepatitis has been reported in many studies (Ng, Low, Wong, Sudin, & Mohamed, ; Wallace, Mcnally, Richmond, Hajarizadeh, & Pitts, ). The feeling of stigmatization revealed in the present study is compatible with the findings of previous qualitative studies showing stigma in patients of HBV infection in Iran (Hassanpourdehkordi et al., ; Valizadeh et al., ). Patients’ stigmatization‐related perceptions and responses vary across communities, diseases (Butt, ) and periods of time.…”
Section: Discussionsupporting
confidence: 92%
“…The noticeable psychological consequences of this study were like the results of another study conducted in Iran, which reported that patients with hepatitis B reported feelings of sadness and concerns about death resulting from the disease (Valizadeh et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and a further six articles provided a qualitative assessment of stigma, typically through either semi-structured interviews or focus group discussions. [35][36][37][38][39][40] The quantitative studies included a total of 15 studies conducted in people living with HBVor in the general population about people living with HBV and two studies that were conducted exclusively in healthcare providers. Seven of these studies assessed stigma exclusively in people living with HBV, 18,22,23,[27][28][29]31 two of which also conducted separate analyses in people without HBV, 23,31 and the remainder were conducted in general population samples.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Marital dissatisfaction has been reported in various chronic diseases such as diabetes (9), chronic renal failure (10), Crohn's disease (11), and multiple sclerosis (12). Although either physical symptoms of this disease or the side effects of treatment have led to reduced quality of marital relations between couples, hepatitis B is seperated from other diseases for several factors including the risk of transmission to sexual partner through unprotected sexual relations and to other healthy members through household contact (3), feeling of social stigma (13), psychological consequences (14), the struggle for self-care (15), and susceptibility to hepatic cirrhosis and hepatocellular carcinoma (16). There has been a growing interest in understanding how chronic illness affects sexual functioning and relationships among chronic patients in the marital dyads (17).…”
Section: Introductionmentioning
confidence: 99%